Cardiovascular mortality of 40–69-year-olds in Sri Lanka from 1980 to 2010: a birth cohort analysis by age and sex - DTH De Silva; EDSM De Alwis; DM De Mel; AHD De Silva; TU Munasinghe; AR Wickremasinghe (BMJ Open)
Objectives To compare cardiovascular mortality (ischaemic heart disease (IHD), hypertensive disease (HTN) and cerebrovascular disease (CeVD)) of 40–69-year-old Sri Lankans from 1980 to 2010 by age, birth cohort and sex.Design A comparative retrospective study.Setting Sri Lanka.Participants 40–69-year-old Sri Lankans from 1980 to 2010.Primary and secondary outcome measures Cardiovascular deaths due to IHD, HTN and CeVD.Results Mortality due to IHD increased with age but decreased with birth cohorts with time (range 3.7–390 per 100 000 population); there was a spike in the IHD mortality rates in both age groups and birth cohorts in 2000. Deaths due to HTN markedly increased after 55 years; however, mortality decreased in the younger cohorts (range 2.8–204.81 per 100 000 population). CeVD mortality linearly increased with age (range 3.3–153.3 per 100 000 population); birth cohorts of 1926–1930 and 1931–1935 had a spike in mortality among the 60–64 and 65–69 age groups, respectively. Changes were seen among both males and females; mortality rates were higher in males than in females.Conclusions All cardiovascular mortality rates increased with age and are higher in males than in females. Age-specific cardiovascular mortality rates were lower in the younger birth cohorts as compared with the older birth cohorts. The increase in cardiovascular deaths in Sri Lanka is due to the ageing population.